Pengaruh Reward dan Punishment Terhadap Kinerja Pegawai - Fitriya Daulina; Achmad Efendi; Damingun (Journal of Trends Economics and Accounting Research, 2024)
The effect of reward and punishment on employee performance at SD Muhammadiyah 1 Samarinda. The formulation of the problem in this study is how the influence of reward and punishment on employee performance at SD Muhammadiyah 1 Samarinda. Based on observations, SD Muhammadiyah 1 Samarinda has a phenomenon related to the reward and punishment system which can be categorized as unclear and often neglected. This study aims to examine and analyze the effect of reward and punishment on employee performance at SD Muhammadiyah 1 Samarinda. The research method used is the quantitative research method. The data analysis technique used is multiple linear regression analysis. Reward is an award that aims to encourage someone to be more diligent in their efforts to improve or increase the achievements they have achieved. Meanwhile, punishment is the provision of punishment to employees who do not act according to applicable rules. The results of the study stated: (1) The reward variable has a positive and significant effect worth 0.013 < 0.05 on employee performance, (2) The punishment variable has a positive and significant effect worth 0.017 < 0.05 on employee performance, (3) The reward and punishment variables simultaneously have a significant effect worth 0.000 < 0.005 on the performance of employees of SD Muhammadiyah 1 Samarinda.